Discursive functions and constructionalization of independent "subordinate" sentences in Spanish - Rodríguez, Catalina Fuentes (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The topic under discussion in this paper is the syntax of sentences introduced by a subordinate conjunction (que, si, como) that have an independent function in the discourse. Some authors have considered them insubordinate clauses. The author discusses the functions they perform in Spanish discourse, especially in reactive turns, and proposes a macrosyntactic approach that includes a range of structural possibilities: independent utterances, conventional constructions, or discursive operators. These possibilities depend on the different degrees of grammaticalization they show: as semi-fixed constructions or pragmatic markers.